Mobile application on real-time highway traffic status in Malaysia / Akmal Irham Asnor - Asnor, Akmal Irham (2019)
This project research is focusing on the Highway Traffic Status mobile application for highway user who always been stuck in heavy traffic. By using the information about highway traffic status that has been posted in social media such as tweeter, this application will extract all the information related to highway traffic, analyze the information and display the information to end user. Even though, there is some application that already been used by the user to get the information about highway traffic statuses such as PLUS Highway Status & Rate, Plus Highway Traffic Status and LLM Traffic. All these applications are not based on real-time information, therefore, the user still facing problem to get the latest highway traffic status. To solve this problem, this project used R programming language since R programming language is one of the best programming languages that often used in data analysis. R programming language is used to extract and analyze all the data so that the user will get the latest information about highway traffic. The working prototype of this project was developed by using Android Studio since Android Studio is an officially Integrated Development Environment (IDE) for Google's Android operating system. The outcome for this project is to create Highway Traffic Status mobile application that provides the latest traffic status to the user.